Pendampingan dan Penyusunan Sistem Laporan Keuangan Koperasi KJKS - Risa Watti; Djojo Dihardjo; Nurul Azizah (Jurnal Kabar Masyarakat, 2024)
Assistance and preparation of financial reporting systems for Sharia Financial Services Cooperatives (KJKS) aim to help cooperatives manage and prepare financial reports in accordance with Sharia principles and applicable accounting standards. Here are the key points from the process: Technical Assistance: The assistance team provides guidance and direction to the cooperative management on the proper way to record and manage financial transactions. This assistance includes understanding Islamic accounting, financial flow, and how to record transactions according to applicable regulations. Preparation of Financial Statements: The main focus of preparing financial statements is to ensure that the cooperative has a good, transparent, and accurate recording system. The financial statements prepared include the balance sheet, income statement (or surplus-deficit), statement of changes in equity, and notes to the financial statements. Implementation of Technology Systems: One important aspect in the preparation of financial statements is the use of supporting technology, such as applications or accounting software specifically designed for sharia cooperatives. This makes it easier for cooperative managers to record digitally, faster, and reduces the risk of manual errors. Compliance with Sharia Principles: The financial statements prepared must adhere to Sharia principles, such as fund management in accordance with Sharia contracts, and must not involve usury. This is important to maintain the trust of cooperative members and ensure the cooperative's operations comply with Islamic law. Training for Managers: The mentoring also includes training for cooperative managers to ensure they can independently manage financial reports after the mentoring is completed. This is important so that the cooperative can maintain its financial system sustainably. With this assistance, it is hoped that KJKS in Surabaya will be able to improve transparency, accountability, and efficiency in financial management, thereby providing greater benefits to its members and supporting the sustainability of the cooperative.